Sala de apoio pedagógico: os sentidos e significados construidos no Município de Barueri - SP - Escabora, Carina (2006)
The aim of this work is to study the meanings and senses of Sala de Apoio Pedagógico in Barueri town in São Paulo state during the years 2002 to 2004, on teacher s perspective. Thus, it was tried to understand how SAP project was defined in Barueri and how its implementation was conducted at schools. It is proposed to investigate major faced difficulties and the results of the project. It deals with an exploratory study that fits in qualitative researches, having as subject teachers that worked in SAP and multidisciplinary teams (specialists). To the accomplishment of this research, we used as resource semistructural interviews, open questions questionnaire and empirical observations. The collected data were organized on table structures to make them clearer. In interviews case, the tables had their cells split in PI and PII, showing the responses of the teachers in the first and second phase, respectively. The results evidenced that the teachers that worked on first phase, were better prepared for the support of learning differences and difficulties better understanding the project, while teachers of second phase had exerted the functions without having the knowledge for it. It also became clear that these teachers felt the support service as another formation moment, and offered reinforcement project attendance like to the students. This work reveals the improvement and change needs and announces new actions that were took by the city to support learning differences and difficulties